Economic efficiency of production of berry semi-finished products using cryoprotectants - Kaminska (Halapsina), Svitlana; Simahina, Galina (My University, 2023)
One of the key factors in assessing the economic efficiency of production is not only the quality of the product, but also the profit from its sale. To calculate the cost of production, it is necessary to determine all costs that occur in the production process (the purchase price of raw materials, wages, electricity and other auxiliary costs related to the business and production activities of the enterprise).
Keywords: кафедра технології оздоровчих продуктів; the economic efficiency; freezing fruit and berry; cost